Perbedaan Reaksi Emosional Antara Olahragawan Body Contact dan Non Body Contact - Sukadiyanto, - (Faculty of Psychology, Universitas Gadjah Mada, 2005)
This research aimed to know the differenceÂ of emotional reaction status between athletes ofÂ body contact and non body contact, and alsoÂ aimed to know the difference of emotional reactionÂ status between boys and girls.Â The research method is survey, and datacollecting by questionnaire which consist ofÂ seven factors, that is desire, assertiveness,Â sensitivity, tension control, confidence, personalÂ accountability, and selfâ€discipline. In each factorconsist of six statement item, three positiveÂ statement and three negative statements.Â Research populations are all athletes inKabupaten Sleman, and with purposiveÂ sampling technique there were 204 boys andÂ girls. Data analyzed by analysis of variancewith level of significance 5%.Â Result of research indicate that: (1) ThereÂ are difference of emotional reaction statusÂ between an athelete of body contact and nonÂ body contact, where an athelete of body contactÂ higher than non body contact, (2) There aredifference of emotional reaction status betweenÂ sportsman of boys and girls, where boys higherÂ than girls, and (3) There is no interactionÂ between the kind of sports and the gender on theemotional reaction status.